Play me a story : a child's introduction to classical music through stories and poems - Rosenberg, Jane, 1949- (New York : A.A. Knopf, 1994)
A collection of poems suggesting images that might be evoked by pieces of classical music, from "The Elephant" in "Carnival of the Animals" to "In the Hall of the Mountain King" in "Peer Gynt."
Disc contains musical selections with narration.
Keywords: Music appreciation -- Juvenile literature; Music -- Juvenile poetry; Children's poetry, American; Music -- Poetry; American poetry